Caffeine citrate maintenance doses effect on extubation and apnea postventilation in preterm infants. Issue 10 (15th July 2020) - Wan, Lijia; Huang, Li; Chen, Pingyang
Abstract: Background: Caffeine citrate is used to prevent apnea in premature infants and help in extubation of invasive ventilation, but the optimal dose remains undetermined. Methods: Neonates born at less than 30 weeks gestation who had received invasive ventilation for at least 48 hours and a loading dose of 20 mg/kg caffeine citrate were randomly assigned into high (10 mg/kg daily) or low (5 mg/kg daily) maintenance dose groups. The drug was discontinued if no apnea occurred for 7 consecutive days. Results: A total of 111 infants were assigned into the high (54) or low (57) dose groups. Extubation failure (16.7% vs 36.8%), age of extubation (8.2 ± 2.1 vs 10.7 ± 2.3 day), duration of invasive ventilation (7.2 ± 2.1 vs 8.5 ± 2.4 day), duration of ventilation before extubation (8.0 ± 1.8 vs 10.1 ± 1.9 day), and number of days of apnea (1.8 ± 1.3 vs 3.2 ± 1.1 day) were significantly lower in the high dose group than the low dose group. Difference in time until failure (6.7 ± 1.7d vs 7.0 ± 1.9d) and duration of nasal continuous positive airway pressure(7.8 ± 1.8 vs 8.0 ± 2.2 day) were not significant. Furthermore, no significant differences in the incidence of tachycardia (9.3% vs 12.3%), abdominal distension (16.7% vs 12.3%), feeding intolerance (3.7% vs 5.3%), or irritability (7.4% vs 5.3%) were observed between groups. Conclusions: A higher maintenance dose of caffeine citrate reduced the incidence of extubation failure and apnea of prematurity without increasing the occurrence of adverse reactions.